(untitled) (Experimental biology, 2015)
Nowadays, many drugs are made from plants. Plants are the source of different organic components. So the great theoretical and practical interest are the search and selection of BAS from plants, as well as use in medicine. the results of the determination of structure and composition, as well as a selection of essential oils of flowers HELIANTNUS TUBERSROSUS. Analysis of a gas chromatograph with a mass spectrum detektrom Agilent 6890/5973N. As a result of the Tashkent region of Jerusalem artichoke flower essential oil output stood at 0.5%, but from Jerusalem artichoke flower of Almaty oblast is 0.37%. The main components are: 1R-Alpha pinene, Alpha pinene and other essential oils